1976
DOI: 10.1080/03601237609372038
|View full text |Cite
|
Sign up to set email alerts
|

Rat urinary metabolites from O, O‐diethyl‐O‐(3, 5, 6‐trichloro‐2‐pyridyl) phosphorothioate

Abstract: Rats metabolized single oral doses of O,O-diethyl-O(3,5,6-trichloro-2-pyridyl-2,6-14C) phosphorothioate to at least six radiolabeled urinary metabolites. The urine contained about 90 percent of the dose. Three of these metabolites were identified as the glucuronide of 3,5,6-trichloro-2-pyridinol (80% the urinary 14C), a glycoside of 3,5,6-trichloro-2-pyridinol (4%), and 3,5,6-trichloro-2-pyridinol (12%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 4 publications
0
32
0
1
Order By: Relevance
“…Carbaryl is a common carbamate insecticide marketed primarily for use on turf and gardens, while naphthalene is used in mothballs and is found in cigarette smoke and petroleum products (Hill et al, 1995a). TCPY is the major metabolite in urine of the pesticides chlorpyrifos, chlorpyrifos-methyl, and triclopyr and has a biological halflife of approximately 27 h (Bakke et al, 1976;Nolan et al, 1984;Hill et al, 1995a). TCPY is also the principal product of environmental degradation of chlorpyrifos and may persist in soil for more than 1 year (Racke et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Carbaryl is a common carbamate insecticide marketed primarily for use on turf and gardens, while naphthalene is used in mothballs and is found in cigarette smoke and petroleum products (Hill et al, 1995a). TCPY is the major metabolite in urine of the pesticides chlorpyrifos, chlorpyrifos-methyl, and triclopyr and has a biological halflife of approximately 27 h (Bakke et al, 1976;Nolan et al, 1984;Hill et al, 1995a). TCPY is also the principal product of environmental degradation of chlorpyrifos and may persist in soil for more than 1 year (Racke et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, an absorption fraction of 1.0 was used in the chlorpyrifos exposure model, with a uniform uncertainty distribution ranging from 0.8 to 1.0 (Table 17) . Nolan et al (1984) reported that in a study on humans, 70% of an ingested dose of chlorpyrifos was absorbed in 48 h. Bakke et al ( 1976) , Ahadaya et al ( 1981) , and Smith et al (1967) found that 90% of an administered dose of in an acute oral exposure was absorbed in rats. Thus, a constant absorption value of 0.7 was used for all simulated individuals and ingested media in the chlorpyrifos exposure model (assumes that the variation between individuals in the population is small) , with a uniform uncertainty distribution ranging from 0.5 to 0.9 (Table 17) .…”
Section: Absorption Factorsmentioning
confidence: 99%
“…Studies in rats indicate that 90% of a single dose of radioactively labeled chlorpyrifos can be recovered from the urine within a day (Bakke et al, 1976;Smith et al, 1966). The major metabolites were identified as 3,5,6-trichloro-2-pyridinal phosphate (75 to 80%), TCP (15 to 29%), and traces of O,O-diethyl-O-3,5,6-trichloro-2-pyridyl phosphorothioate.…”
Section: Adipose Tissuesmentioning
confidence: 98%